What Drives the Tax Avoidance in Mining Firms? - Ni Wayan Damayanti; Anak Agung Putu Gede Bagus Arie Susandya (Philippine Social Science Journal, 2025)
This study empirically examines the influence of Corporate Social Responsibility (CSR), leverage, profitability, and company size on tax avoidance among mining firms listed on the Indonesia Stock Exchange. Using multiple regression analysis, the findings demonstrate that CSR, leverage, and profitability all negatively affect tax avoidance, indicating that firms prioritize social legitimacy and financial stability over aggressive tax minimization strategies. Conversely, company size showed no significant impact on avoidance practices. These results highlight the necessity of balancing capital structure with regulatory compliance and suggest that future research should incorporate audit quality as a moderating variable to provide a deeper understanding of these mechanisms.